Cultural diplomacy of the State Department as a tool of US foreign policy: the "Golden Age" (1953 – 1961 years) - Klynina, Tetiana (Ukrainian Cultural Studies, 2022)
The article is devoted to the consideration of the issue of the development of US cultural diplomacy in 1953-1961 as a tool for implementing foreign policy. In American historiography, it is customary to describe this period as the "golden age", since there was a significant breakthrough in the understanding of the importance of culture as one of the effective elements of the implementation of US foreign policy. The methodological basis of the article was the principle of historicism, a systematic approach, problem-chronological and descriptive methods. The purpose of the article is to analyze the main types of cultural diplomacy that the USA used to promote itself abroad in the context of the confrontation with the Soviet Union. The article emphasizes the problem of comparing the concepts of "cultural diplomacy" and "public diplomacy", which makes it difficult to understand their organizational histories. The author of the article starts from the position that "cultural diplomacy" is not separate from "public diplomacy" and is an integral part of it. It is emphasized that the development of the Cold War and the Soviet Union’s representation of itself as a country with a great cultural heritage and potential posed the question of changing cultural policy before the US government. During the presidency of D. Eisenhower, dance tours, art exhibitions, cinematography, literature, musical performances, educational, scientific and cultural exchange programs were transformed from an element of exclusively American art into instruments of foreign policy. Not the last role in this transformation was played by the US State Department and, created later, the US Information Agency. Although at the same time, both institutions tried to avoid full responsibility for the results of cultural policy implementation. The basis for this attitude was the constant criticism of congressmen (among whom J. McCarthy played a significant and rather harmful role), as well as the focused attention of the American public on the appropriateness of using the money of American taxpayers. The article refutes the thesis that art in the United States was outside of politics and proves that culture has been in step with the US foreign policy course. Nevertheless, despite a number of obstacles and state control, the cultural diplomacy of D. Eisenhower’s time appeared in other colors and really became its "golden period".